Balancing Act: Integrating Qualitative And Quantitative Data Driven For Recruitment And Selection Process - Paudel, Ram; Sanaz Tehrani; Alex Sherm (SEAN Institute, 2024)
The research in question delves into the intricate realm of recruitment and selection methods, examining the relationship between qualitative and quantitative approaches. It delves into specific scenarios where each method shines, underscoring the importance of flexibility and integration in decision-making processes. Through a thorough examination, the study underscores the advantages of amalgamating qualitative insights with quantitative data to attain a comprehensive candidate evaluation. By addressing biases and subjectivity, this technique seeks to enhance the fairness and efficiency of recruitment and selection procedures. Ultimately, the research contributes to a broader comprehension of how organizations can fine-tune their recruitment strategies to meet the evolving demands of the job market while ensuring impartial and well-informed decision-making.